Preparation of Composite Reinforced Agent Based on Sweet Sorghum Stalk Fiber through Alkali Pressure Steam Treated Method (Universitas Negeri Semarang, 2022)
Increasing global concern to environmental issues and sustainability related to preservation of non-renewable natural resources has encouraged research to develop new environmental friendly materials and products based on renewable natural resources. Sorghum fiber has potential to be a composite reinforcement because it has a good mechanical properties, environmental friendly and inexpensive. The preparation process of sorghum fiber is needed to improve its compatibility with polypropylene (PP). Thermal alkalization is the method used in conducting fiber preparation. In this study, alkalization-thermal treatment with 0%, 5% and 10% NaOH and pressurized steam for 1 and 3 minutes was carried out to change the hydrophobicity of sorghum fiber. The most optimum result was obtained at 5% NaOH concentration with 3 minutes pressure-soaking, showing cleaner and fibrillated morphology based on FESEM testing. It was less lignin and hemicellulose content as indicated by FTIR testing result, better hydrophobicity as indicated through Sessil Drop testing result that showed contact angle of 120.9◦, as well as significant increase in crystallinity index of 6.3% as indicated through X-Ray Diffraction (XRD) test result. The increase in the hydrophobicity of the modified sorghum fiber indicated the increase of the natural fiber compatibility with polymer matrix.